The Property Rights Theory Approach from a Socio-Economic Viewpoint - Baranowski, Mariusz (Studia Historiae Oeconomicae, 2011)
This paper examines the property rights theory as a part of the New Institutional Economics. It uses the socioeconomic perspective to capture advantages and disadvantages of this theory in the context of economic effectiveness of a company (practical issue), as well as the usefulness of its analytical tools (theoretical issue).